Monitoring the progression of erosive tooth wear (ETW) using BEWE index in casts and their 3D images: A retrospective longitudinal study. (June 2018) - Marro, Francisca; De Lat, Liesa; Martens, Luc; Jacquet, Wolfgang; Bottenberg, Peter
Abstract: Objective: To determine if the Basic erosive tooth wear index (BEWE index) is able to assess and monitor ETW changes in two consecutive cast models, and detect methodological differences when using the corresponding 3D image replicas. Methods: A total of 480 pre-treatment and 2-year post-treatment orthodontic models (n = 240 cast models and n = 240 3D image replicas) from 120 adolescents treated between 2002 and 2013 at the Gent Dental Clinic, Belgium, were scored using the BEWE index. For data analysis only posterior sextants were considered, and inter-method differences were evaluated using Wilcoxon Signed Rank test, Kappa values and Mc Nemar tests (p < 0.05). Correlations between methods were determined using Kendall tau correlation test. Results: Significant changes of ETW were detected between two consecutive models when BEWE index was used to score cast models or their 3D image replicas (p < 0.001). A strong significant correlation (τb: 0.74; p < 0.001) was shown between both methods However, 3D image-BEWE index combination showed a higher probability for detecting initial surface changes, and scored significantly higher than casts (p < 0.001). Incidence and progression of ETW using 3D images was 13.3% (n = 16) and 60.9% (n = 56) respectively, with two subjects developing BEWE = 3 in at least one tooth surface. Conclusions: BEWE index is a suitable tool for the scoring of ETW lesions in 3D images and cast. The combination of both digital 3D records and index, can be used for the monitoring of ETW in a longitudinal approach. The higher sensibility of BEWE index when scoring 3D images might improve the early diagnosis of ETW lesions. Clinical significance: The BEWE index combined with digital 3D records of oral conditions might improve the practitioner performance with respect to early diagnosis, monitoring and managing ETW.